Construct validity of the internalizing and externalizing problems questionnaire for children - Romero Godínez, Edith; Lucio Gómez-Maqueo, Emilia; Durán Patiño, Consuelo (Acta Universitaria, 2019)
The empirical classification systems developed for the diagnosis of infant psychopathology establish two broad dimensions: internalizing and externalizing problems (IP & EP). The aim of this study was to determine the psychometric properties of the internalizing and externalizing problems scale for children (CPIEN, from its acronym in Spanish) to obtain a valid and reliable tool that help identify these problems in children from 8 to 12 years old (M = 9, SD = 1.1). Participants were 364 girls and 344 boys from elementary schools in Mexico City. The instrument was administered in classrooms, prior authorization from parents and school authorities. A confirmatory factor analysis (CFA) was performed through the AMOS 21 software. The results showed good fit for the models; the Cronbach’s alpha coefficient (α) was also obtained (0.86). This confirmed the factorial structure of two dimensions. The Scale is a valid and reliable measure, useful to assess children with IP & EP.